Study of the Effects of Nonlinear Potential Sweeps on Voltammetry - Ogurtsov, V.; Beni, V.; Strutwolf, J.; Arrigan, Damien (Wiley - VCH Verlag GmbH & Co. KGaA, 2009)
Voltammetric methods use a constant sweep rate during the course of a scan. This paper reports a study of the influence of a nonconstant sweep rate on the voltammetric response. In this approach, either continuously increasing or continuously decreasing potential scan rates can be employed, unlike presently available methods which rely on a constant sweep rate. The voltammetric response of potassium ferrocyanide at a glassy carbon electrode was used as a model system to test the new method. The responses obtained using traditional staircase voltammetry (linear staircase voltammetry) and the new approach (nonlinear staircase voltammetry) were compared by experiment and by simulation. The new approach offers capability for signal enhancement, whereby enhanced current or enhanced peak shape can be obtained by choice of appropriate waveform parameters.